Cervical Cancer Chemoprevention Using Hippobroma longiflora Extract through Modulation of Ki-67 and p53 in Benzo[a]pyrene-Induced Wistar Rats - Ana Bina Sari; Eman Sutrisna; Daniel Joko Wahyono (Althea Medical Journal, 2026)
Background: Cervical cancer remains one of the most common malignancies affecting women worldwide and is closely linked to dysregulated cell proliferation and impaired tumor suppressor responses. Herbs contain effective anticancer compounds that may be used alone or as adjuvants to existing chemotherapy regimens to improve efficacy and/or reduce drug-induced toxicity. Hippobroma longiflora (L.) G.Don a or kitolod is a medicinal plant known to contain antioxidant and anticancer compounds. This study evaluated the effect of ethanol extract of kitolod leaves on Ki-67 and p53 expression in a Benzo[a]pyrene (B[a]P)-induced cervical carcinogenesis model in female Wistar rats.Methods: This experimental study used a post-test-only control group design. Female Wistar rats (n=25) were grouped into five groups: a healthy control group without B[a]P exposure, a negative control group receiving only B[a]P (0.3 mg/kg BW/day); and three treatment groups receiving B[a]P combined with kitolod leaf extract at doses of 100, 200, or 300 mg/kg BW/day for 30 days. Phytochemical screening and gas chromatography–mass spectrometry (GC-MS) were used to characterize the extract. Cervical histopathologal and immunohistochemical examinations were performed to assess Ki-67 and p53 expression. Data were analyzed using one-way ANOVA followed by Bonferroni post hoc tests, with p<0.05 considered statistically significant.Results: Compared with the negative control, kitolod leaf extract significantly reduced Ki-67 expression and increased p53 expression (p<0.001). The greatest effect was observed at the 300 mg/kg BW/day dose. Conclusions: Kitolod leaf ethanol extract modulates Ki-67 and p53 expression in B[a]P-exposed rats, suggesting anti-proliferative activity and enhancement of tumor suppressor responses during early cervical carcinogenesis.